Preparation method of isoniazide electrochemical biosensor

By modifying the 2,3-di-pyrophidine binary acid and β-cycle paste to the branches of the branches of the branches on the golden electrodes, a stable self-assembly film is formed, and the problem of high electrode reaction potential in the existing technology is too high and low-sensitivity. , Realize the high -sensitivity test of different smoke.

CN119355084APending Publication Date: 2025-01-24QILU SCHOOL OF MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411923803.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, when detecting isoniazid, the electrode reaction potential is too high and the sensitivity is low, making it difficult to meet the needs of efficient detection.

Method used

By modifying the 2,3-di-pyrophodidicic acid and β-cycle paste on the golden electrode, a stable self-assembly film is formed to increase the electrode conductivity, surface area and stability, thereby increasing the electrode Detection performance.

Benefits of technology

A high sensitivity testing of different smoke is achieved, the current response is significantly improved, the detection performance is significantly improved, and it is suitable for the measurement of the alien cigarette content in clinical testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355084A_ABST
    Figure CN119355084A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biochemical electrodes, and particularly relates to a preparation method of an isoniazide electrochemical biosensor. Pretreating the gold electrode to obtain a bare gold electrode; soaking the bare gold electrode in a 2, 3-dimercaptosuccinic acid solution in a suspension manner, taking out the bare gold electrode, washing the bare gold electrode, and airing the bare gold electrode to obtain a gold electrode modified by the 2, 3-dimercaptosuccinic acid; adding beta-cyclodextrin and refined chitosan into an HCl solution, and uniformly stirring to obtain a milk white solution; heating the milky white solution until the solution is colorless, then adding glutaraldehyde for reaction, adjusting the pH value, cooling, precipitating and filtering to obtain beta-cyclodextrin grafted chitosan; and adding the 2, 3-dimercaptosuccinic acid modified gold electrode into a mixed solution of beta-cyclodextrin grafted chitosan and a cross-linking agent for soaking, washing and airing to obtain the isoniazide electrochemical biosensor. The isoniazide electrochemical biosensor prepared by the invention can promote electron transfer, and the current response of the electrode is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biochemical electrodes, and in particular relates to a method for preparing an isoniazid electrochemical biosensor. Background Art

[0002] Tuberculosis is a disease caused by infection with Mycobacterium tuberculosis. It is usually more common in pulmonary tuberculosis. It is an infectious disease. In recent years, extrapulmonary tuberculosis infection and atypical tuberculosis have become more common. In the treatment of tuberculosis, isoniazid is still the first-line anti-tuberculosis drug recommended by the World Health Organization and is irreplaceable. Isoniazid (4-pyridinecarboxyhydrazide), also known as remifen, has a killing effect on both intracellular and extracellular tuberculosis bacteria. The drug has strong medicinal properties, high concentration, and fast action, and can quickly reach a bactericidal concentration; however, the incidence of adverse drug reactions in the anti-tuberculosis regimen is high, and patients need to take medication for a long time, resulting in poor tolerance to treatment. Therefore, the research on the chemical analysis and detection method of isoniazid is of great significance in the fields of drug analysis and clinical medicine.

[0003] At present, the methods for determining the concentration of isoniazid include fluorescence spectrophotometry, flow injection chemiluminescence, high performance liquid chromatography, fluorescence analysis, resonance light scattering spectroscopy, electrochemical sensor method, etc. Among them, the use of electrochemical sensor method to detect drugs can make up for some shortcomings of traditional detection methods. Electrochemical sensor method for drug detection has the advantages of fast analysis speed, convenient operation, short response time, low price, high sensitivity, etc., and has always occupied an important position in scientific research, education, production and life.

[0004] Isoniazid itself has a certain electrochemical activity and can be directly detected by electrochemical methods. However, when isoniazid is directly detected on the surface of a traditional solid electrode, the potential of the electrode reaction is too high and the sensitivity is very low. Therefore, people have prepared a variety of chemically modified electrodes to improve their performance, stability, sensitivity, etc. 2,3-dimercaptosuccinic acid (DMSA) is the most promising and effective drug in metal complexation. It is distributed outside the cell, so its toxicity may be lower than that of other dithiol drugs.

[0005] Many scholars at home and abroad are committed to the research and application of cyclodextrin (CD) modified electrodes in analysis. CD is a substance with a special structure of internal hydrophobic and external hydrophilic. It can form inclusion complexes with other molecules and is used as a chiral selector. β-cyclodextrin (β-CD) is one of the derivatives of cyclodextrin. It can selectively combine with target molecules through some intermolecular forces to form a stable host-guest inclusion complex, so it has good molecular recognition performance. Chitosan (chitosan, CTS) has the characteristics of wide source, low price, non-toxic and harmless, biodegradable and gel-forming. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an isoniazid electrochemical biosensor. The prepared isoniazid electrochemical biosensor can promote the transfer of electrons and significantly improve the current response of the electrode.

[0007] The preparation method of the isoniazid electrochemical biosensor of the present invention comprises the following steps: (1) After pretreatment, the gold electrode is obtained as a bare gold electrode; (2) Suspending and immersing the bare gold electrode in a 2,3-dimercaptosuccinic acid solution, taking it out, rinsing it, and then drying it to obtain a 2,3-dimercaptosuccinic acid-modified gold electrode; (3) adding β-cyclodextrin and refined chitosan to HCl solution and stirring evenly to obtain a milky white solution; heating the milky white solution until it becomes colorless, adding glutaraldehyde to react, adjusting the pH value, cooling, precipitating, and filtering to obtain β-cyclodextrin grafted chitosan; (4) The gold electrode modified with 2,3-dimercaptosuccinic acid is added to a mixed solution of β-cyclodextrin grafted chitosan and a crosslinking agent, immersed, washed, and dried to obtain an isoniazid electrochemical biosensor.

[0008] The pretreatment in step (1) is performed in sequence: grinding, polishing, first ultrasonic cleaning, drying, second ultrasonic cleaning and rinsing.

[0009] In step (2), the suspension soaking temperature is 3.5-4.5° C., and the suspension soaking time is 22-26 h. The concentration of the 2,3-dimercaptosuccinic acid solution is 0.018-0.022 mol / L.

[0010] In step (3), the ratio of β-cyclodextrin, refined chitosan, HCl solution and glutaraldehyde is 2.9-3.1:0.9-1.1:149-151:3.9-4.1, wherein β-cyclodextrin and refined chitosan are both measured in g, and HCl solution and glutaraldehyde are both measured in mL.

[0011] In step (3), the concentration of the HCl solution is 0.95-1.05 mol / L, and the concentration of glutaraldehyde is 48-52 wt.%.

[0012] In step (3), the heating temperature is 84-86°C, and the heating time is 28-32 min; the reaction temperature is 83-85°C, and the reaction time is 1-1.1 h; and the pH value is adjusted to 7.9-8.1.

[0013] In step (4), the mixed solution of β-cyclodextrin grafted chitosan and a crosslinking agent is prepared by mixing β-cyclodextrin grafted chitosan and a crosslinking agent, wherein the mass ratio of β-cyclodextrin grafted chitosan to the crosslinking agent is 1:1.1-1.2.

[0014] In step (4), the cross-linking agent is a mixed solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and N-hydroxysuccinimide (NHS), wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 0.18-0.22 mol / L, and the concentration of N-hydroxysuccinimide is 0.018-0.022 mol / L.

[0015] The preparation method of the cross-linking agent in step (4) is to dissolve 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a phosphate buffer solution to obtain the cross-linking agent.

[0016] The soaking time in step (4) is 22-26 hours.

[0017] The present invention first modifies 2,3-dimercaptosuccinic acid on a gold electrode, and the thiol group on DMSA forms a stable Au-S bond with the gold electrode to form a dense adsorption layer, and then the beta-cyclodextrin grafted chitosan is cross-linked to the modified gold electrode through a cross-linking agent. The invention has the advantages of having both the adsorption properties of chitosan and the inclusion properties of cyclodextrin, having stronger adsorption capacity, being able to be well adsorbed on the surface of the gold electrode, and increasing the conductivity, surface area and stability of the electrode.

[0018] The preparation mechanism of the present invention is as follows:

[0019] The preparation reaction equation of β-cyclodextrin grafted chitosan is as follows: H2N-Chiosan-NH2+OHCCH2CH2CH2CHO+HO-CD→H2N-Chitosan-N=CHCH2CH2CH2CHOHO-CD The preparation mechanism of β-cyclodextrin grafted chitosan is that there are a large number of active hydroxyl groups and amino groups in chitosan molecules, and cyclodextrin molecules also have a large number of hydroxyl groups. One aldehyde group in glutaraldehyde is connected to the amino group on chitosan through a Schiff base reaction, and the other aldehyde group in glutaraldehyde is connected to the hydroxyl group of β-cyclodextrin through an acetal reaction to obtain β-cyclodextrin grafted chitosan.

[0020] Self-assembling 2,3-dimercaptoethanediol on the surface of the gold electrode can form a stable monomolecular modification layer. Since the DMSA molecule is connected to the electrode surface through the two thiol groups it contains, it is more solid and stable than other self-assembled films. At the same time, DMSA is also a heavy metal detoxifier with low toxicity and high efficacy. It can react with heavy metals in animals to form a very stable complex, and has the characteristics of fast absorption, fast excretion, and no accumulation. β-cyclodextrin grafted chitosan has both the adsorption capacity of chitosan and the inclusion properties of cyclodextrin, and has a stronger adsorption capacity. 2,3-dimercaptoethanediol and β-cyclodextrin grafted chitosan are modified on the gold electrode at the same time. The thiol group can form a stable chemical bond with the surface of the gold electrode. Compared with other modified substances, the self-assembled film formed is more solid and stable. After the β-cyclodextrin grafted chitosan is modified, the contact area is increased, which can significantly improve the detection rate of the electrode, bringing higher efficiency to the detection, making the detection more convenient and quick.

[0021] β-cyclodextrin grafted chitosan has both the envelope recognition, controlled release and electron transport properties of cyclodextrin and the good biocompatibility, non-toxicity and biodegradability of chitosan; the thiol groups in 2,3-dimercaptosuccinic acid can self-assemble to the surface of the gold electrode through gold-sulfur bonds to form a stable self-assembled film, which improves the stability of the bare gold electrode and increases the surface area of ​​the bare gold electrode. The carboxyl groups in 2,3-dimercaptosuccinic acid and the amino groups of β-cyclodextrin grafted chitosan were co-modified on the gold electrode using the crosslinking agent EDC / NHS to prepare an isoniazid electrochemical biosensor. The conductive film formed not only has excellent electroactivity and electrocatalytic properties, but also can effectively promote electron transfer on the electrode, improve the sensitivity of the biosensor, and thus achieve more accurate detection of specific analytes.

[0022] The beneficial effects of the present invention are as follows: The present invention provides an isoniazid electrochemical biosensor based on 2,3-dimercaptosuccinic acid / β-cyclodextrin grafted chitosan self-assembly, and the isoniazid electrochemical biosensor is prepared by modifying β-cyclodextrin grafted chitosan onto a gold electrode modified with 2,3-dimercaptosuccinic acid after self-assembly using a crosslinking agent. The gold electrode is modified with 2,3-dimercaptosuccinic acid and β-cyclodextrin grafted chitosan to increase the electrode contact area, promote the electron transfer of isoniazid on the electrode, and improve the detection performance. The best detection conditions were selected through optimization experiments: 0.10 mol / L phosphate buffer solution (pH=4.00) was used, and the peak current of isoniazid was best detected under the condition of a pulse period of 0.6s. The current size of the prepared isoniazid electrochemical sensor increases with the increase of isoniazid concentration within a certain range, and at 1.0×10 -4 -6.0×10 -4mol / L range, the linear regression equation is y=1.0234x+8.4947, and the correlation coefficient is R 2 The value is 0.9951, and the precision, stability and anti-interference performance are good. The current of the isoniazid electrochemical sensor shows an upward trend with the increase of isoniazid concentration, which provides important reference information for measuring the isoniazid content in clinical test drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cyclic voltammetry characterization diagram of the bare gold electrode, the gold electrode modified with 2,3-dimercaptosuccinic acid, and the isoniazid electrochemical biosensor in Example 1; in the figure, a, bare gold electrode, b, 2,3-dimercaptosuccinic acid modified gold electrode, c, isoniazid electrochemical biosensor.

[0024] Figure 2 This is the infrared spectrum of chitosan.

[0025] Figure 3 This is the infrared spectrum of β-cyclodextrin.

[0026] Figure 4 This is the infrared spectrum of the β-cyclodextrin grafted chitosan of Example 1.

[0027] Figure 5 These are the differential pulse voltammograms under different pulse periods, in the figure, a, 0.7s, b, 0.3s, c, 0.4s, d, 0.5s, e, 0.6s.

[0028] Figure 6 These are the differential pulse voltammograms of phosphate buffer solutions with different concentrations. In the figure, a, 0.10 mol / L, b, 0.25 mol / L, c, 0.20 mol / L, d, 0.15 mol / L, e, 0.05 mol / L.

[0029] Figure 7 These are differential pulse voltammograms at different pH values. In the figure, a, pH=7, b, pH=6, c, pH=5, d, pH=3, and e, pH=4.

[0030] Figure 8 This is the standard curve of the isoniazid electrochemical biosensor. DETAILED DESCRIPTION

[0031] The present invention is further described below with reference to the embodiments.

[0032] Example 1 (1) Grind the gold electrode (core diameter of 1 mm) with sandpaper, and then polish it to a mirror surface with Al2O3 polishing powder with a particle size of 0.05 μm, perform the first ultrasonic cleaning with distilled water for 15 min, take it out and dry it naturally, and then perform the second ultrasonic cleaning with anhydrous ethanol for 10 min, take it out and rinse the electrode surface with distilled water and store it for later use, to obtain a bare gold electrode; Potassium ferrocyanide, potassium chloride and distilled water were prepared to 2.5 × 10 -3 mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), transfer to a brown reagent bottle and store for later use; At a potential between -0.2 and 0.6 V, place the bare gold electrode on a 2.5×10 -3 In a mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), the bare gold electrode is scanned by cyclic voltammetry (CV). The potential difference of the bare gold electrode should be within 100 mV, indicating that the bare gold electrode has been treated well. (2) Sodium dihydrogen phosphate solid and distilled water are prepared into a sodium dihydrogen phosphate solution with a concentration of 0.10 mol / L, and phosphoric acid and distilled water are prepared into a phosphoric acid solution with a concentration of 0.10 mol / L. 98.70 ml of the 0.10 mol / L sodium dihydrogen phosphate solution and 1.30 ml of the 0.10 mol / L phosphoric acid solution are mixed evenly, and the pH value is adjusted to 4 to obtain a phosphate buffer solution (pH = 4); 2,3-dimercaptosuccinic acid and phosphate buffer solution are prepared into a 2,3-dimercaptosuccinic acid solution with a concentration of 0.02 mol / L; The bare gold electrode was suspended and immersed in a 0.02 mol / L 2,3-dimercaptosuccinic acid solution at 4°C for 24 h, and then washed with a phosphate buffer solution (pH = 4) and naturally dried to obtain a 2,3-dimercaptosuccinic acid-modified gold electrode. The 2,3-dimercaptosuccinic acid-modified gold electrode was placed on a 2.5×10 -3 mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride) was characterized by cyclic voltammetry; (3) Dissolve chitosan in 1 wt.% acetic acid solution and stir to obtain a white paste, then add 30 wt.% NaOH solution to neutralize until no more precipitation occurs, then adjust the pH value to neutral, wash with distilled water for several times, soak in acetone for 20 h, filter, and dry in an oven at 45 °C for 36 h to obtain refined chitosan; 2.9982 g of β-cyclodextrin and 0.9953 g of refined chitosan were dissolved in 150 mL of 1 mol / L HCl solution, stirred evenly to obtain a milky white solution, heated at 84°C for 30 min until colorless, 4 mL of 50 wt.% glutaraldehyde was added dropwise at 84°C, and after reacting for 1.05 h, the solution became a light yellow solution, and the pH value was adjusted to 8 with 1 mol / L NaOH solution, and the color of the solution became darker, cooled, precipitated, and filtered to obtain β-cyclodextrin grafted chitosan, and the structure of β-cyclodextrin grafted chitosan was characterized by infrared spectroscopy; (4) dissolving 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a phosphate buffer solution (pH=4) to prepare a cross-linking agent, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 0.20 mol / L, and the concentration of N-hydroxysuccinimide is 0.02 mol / L; The β-cyclodextrin grafted chitosan and the cross-linking agent are mixed to prepare a mixed solution of the β-cyclodextrin grafted chitosan and the cross-linking agent, wherein the mass ratio of the β-cyclodextrin grafted chitosan to the cross-linking agent is 1:1.1; The gold electrode modified with 2,3-dimercaptosuccinic acid was rinsed with phosphate buffer solution (pH = 4), then immersed in a mixed solution of β-cyclodextrin grafted chitosan and a crosslinker for 24 h, washed with phosphate buffer solution (pH = 4), and dried to obtain an isoniazid electrochemical biosensor. -3 The characterization was carried out by cyclic voltammetry (CV) in a 0.10 mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride).

[0033] Example 2 (1) Grind the gold electrode (core diameter of 1 mm) with sandpaper, and then polish it to a mirror surface with Al2O3 polishing powder with a particle size of 0.05 μm, perform the first ultrasonic cleaning with distilled water for 15 min, take it out and dry it naturally, and then perform the second ultrasonic cleaning with anhydrous ethanol for 10 min, take it out and rinse the electrode surface with distilled water and store it for later use, to obtain a bare gold electrode; Potassium ferrocyanide, potassium chloride and distilled water were prepared to 2.5 × 10 -3 mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), transfer to a brown reagent bottle and store for later use; At a potential between -0.2 and 0.6 V, place the bare gold electrode on a 2.5×10 -3 In a mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), the bare gold electrode is scanned by cyclic voltammetry (CV). The potential difference of the bare gold electrode should be within 100 mV, indicating that the bare gold electrode has been treated well. (2) Sodium dihydrogen phosphate solid and distilled water are prepared into a sodium dihydrogen phosphate solution with a concentration of 0.10 mol / L, and phosphoric acid and distilled water are prepared into a phosphoric acid solution with a concentration of 0.10 mol / L. 98.70 ml of the 0.10 mol / L sodium dihydrogen phosphate solution and 1.30 ml of the 0.10 mol / L phosphoric acid solution are mixed evenly, and the pH value is adjusted to 4 to obtain a phosphate buffer solution (pH = 4); 2,3-dimercaptosuccinic acid and phosphate buffer solution are prepared into a 2,3-dimercaptosuccinic acid solution with a concentration of 0.018 mol / L; The bare gold electrode was suspended and immersed in a 0.018 mol / L 2,3-dimercaptosuccinic acid solution at 3.5°C for 26 hours, and then taken out and rinsed with a phosphate buffer solution (pH=4) and naturally dried to obtain a 2,3-dimercaptosuccinic acid-modified gold electrode; (3) Dissolve chitosan in 1 wt.% acetic acid solution and stir to obtain a white paste, then add 30 wt.% NaOH solution to neutralize until no more precipitation occurs, then adjust the pH value to neutral, wash with distilled water for several times, soak in acetone for 20 h, filter, and dry in an oven at 45 °C for 36 h to obtain refined chitosan; 2.9 g of β-cyclodextrin and 0.9 g of refined chitosan were dissolved in 149 mL of 1.05 mol / L HCl solution, stirred evenly to obtain a milky white solution, heated at 85°C for 32 min until colorless, 3.9 mL of 52 wt.% glutaraldehyde was added dropwise at 83°C, and after reacting for 1.1 h, the solution turned into a light yellow solution, and the pH value was adjusted to 7.9 with 1 mol / L NaOH solution, the solution color became darker, cooled, precipitated, and filtered to obtain β-cyclodextrin grafted chitosan; (4) dissolving 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a phosphate buffer solution (pH=4) to prepare a cross-linking agent, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 0.18 mol / L, and the concentration of N-hydroxysuccinimide is 0.018 mol / L; The β-cyclodextrin grafted chitosan and the cross-linking agent are mixed to prepare a mixed solution of the β-cyclodextrin grafted chitosan and the cross-linking agent, wherein the mass ratio of the β-cyclodextrin grafted chitosan to the cross-linking agent is 1:1.2; The gold electrode modified with 2,3-dimercaptosuccinic acid was rinsed with a phosphate buffer solution (pH=4), immersed in a mixed solution of β-cyclodextrin grafted chitosan and a crosslinking agent for 22 hours, washed with a phosphate buffer solution (pH=4), and dried to obtain an isoniazid electrochemical biosensor.

[0034] Example 3 (1) Grind the gold electrode (core diameter of 1 mm) with sandpaper, and then polish it to a mirror surface with Al2O3 polishing powder with a particle size of 0.05 μm, perform the first ultrasonic cleaning with distilled water for 15 min, take it out and dry it naturally, and then perform the second ultrasonic cleaning with anhydrous ethanol for 10 min, take it out and rinse the electrode surface with distilled water and store it for later use, to obtain a bare gold electrode; Potassium ferrocyanide, potassium chloride and distilled water were prepared to 2.5 × 10 -3 mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), transfer to a brown reagent bottle and store for later use; At a potential between -0.2 and 0.6 V, place the bare gold electrode on a 2.5×10 -3 In a mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), the bare gold electrode is scanned by cyclic voltammetry (CV). The potential difference of the bare gold electrode should be within 100 mV, indicating that the bare gold electrode has been treated well. (2) Sodium dihydrogen phosphate solid and distilled water are prepared into a sodium dihydrogen phosphate solution with a concentration of 0.10 mol / L, and phosphoric acid and distilled water are prepared into a phosphoric acid solution with a concentration of 0.10 mol / L. 98.70 ml of the 0.10 mol / L sodium dihydrogen phosphate solution and 1.30 ml of the 0.10 mol / L phosphoric acid solution are mixed evenly, and the pH value is adjusted to 4 to obtain a phosphate buffer solution (pH = 4); 2,3-dimercaptosuccinic acid and phosphate buffer solution are prepared into a 2,3-dimercaptosuccinic acid solution with a concentration of 0.022 mol / L; The bare gold electrode was suspended and immersed in a 0.022 mol / L 2,3-dimercaptosuccinic acid solution at 4.5°C for 22 hours, and then taken out and rinsed with a phosphate buffer solution (pH=4) and naturally dried to obtain a 2,3-dimercaptosuccinic acid-modified gold electrode; (3) Dissolve chitosan in 1 wt.% acetic acid solution and stir to obtain a white paste, then add 30 wt.% NaOH solution to neutralize until no more precipitation occurs, then adjust the pH value to neutral, wash with distilled water for several times, soak in acetone for 20 h, filter, and dry in an oven at 45 °C for 36 h to obtain refined chitosan; 3.1 g of β-cyclodextrin and 1.1 g of refined chitosan were dissolved in 151 mL of 0.95 mol / L HCl solution, stirred evenly to obtain a milky white solution, heated at 86°C for 28 min until colorless, 4.1 mL of 48 wt.% glutaraldehyde was added dropwise at 85°C, and after reacting for 1 h, the solution turned into a light yellow solution, and the pH value was adjusted to 8.1 with 1 mol / L NaOH solution, the solution color became darker, cooled, precipitated, and filtered to obtain β-cyclodextrin grafted chitosan; (4) dissolving 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a phosphate buffer solution (pH=4) to prepare a cross-linking agent, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 0.22 mol / L, and the concentration of N-hydroxysuccinimide is 0.022 mol / L; The β-cyclodextrin grafted chitosan and the crosslinking agent are mixed to prepare a mixed solution of the β-cyclodextrin grafted chitosan and the crosslinking agent, wherein the mass ratio of the β-cyclodextrin grafted chitosan to the crosslinking agent is 1:1.15; The gold electrode modified with 2,3-dimercaptosuccinic acid was rinsed with a phosphate buffer solution (pH=4), immersed in a mixed solution of β-cyclodextrin grafted chitosan and a crosslinker for 26 hours, washed with a phosphate buffer solution (pH=4), and dried to obtain an isoniazid electrochemical biosensor.

[0035] Electrode Characterization: The bare gold electrode, 2,3-dimercaptosuccinic acid-modified gold electrode, and isoniazid electrochemical biosensor (2,3-dimercaptosuccinic acid / cyclodextrin grafted chitosan self-assembled gold electrode) in Example 1 were used as working electrodes, saturated calomel electrode was used as reference electrode, and platinum electrode was used as auxiliary electrode. -3 mol / L potassium ferrocyanide solution (containing 0.10 mol / L potassium chloride), cyclic voltammetry was performed at a potential between -0.2 and 0.6 V. The characterization results are shown in Figure 1 .

[0036] from Figure 1 It can be seen that within the potential range of -0.2-0.6 V, curve a has two peaks, one above and one below, indicating that potassium ferrocyanide undergoes a redox reaction on the surface of the bare gold electrode; the peak current of curve b is higher than that of curve a, indicating that 2,3-dimercaptosuccinic acid is successfully modified on the surface of the bare gold electrode, and 2,3-dimercaptosuccinic acid promotes the migration of electrons; the peak current of curve c is significantly higher than that of curve b, indicating that the isoniazid electrochemical biosensor is successfully prepared, and the modified material on the surface of the bare gold electrode promotes the migration of electrons.

[0037] Structural characterization of β-cyclodextrin grafted chitosan: The structures of chitosan, β-cyclodextrin and β-cyclodextrin grafted chitosan of Example 1 were characterized by Fourier transform infrared spectrometer. The infrared spectrum of chitosan is shown in Figure 2 The infrared spectrum of β-cyclodextrin is shown in Figure 3 The infrared spectrum of the β-cyclodextrin grafted chitosan of Example 1 is shown in Figure 4 .

[0038] from Figure 2It can be seen that at a wavelength of 896.01 cm -1 The characteristic peak of β-(1,4) glycosidic bond appeared at Figure 3 It can be seen that the characteristic peak of the α-(1,4) glycosidic bond structure in β-cyclodextrin appears at a wavelength of 756.13 cm -1 The characteristic peak of D-(1,4) pyranose structure appears at a wavelength of 706.94 cm -1 From Figure 4 It can be seen that at wavelengths 1048, 859, 759 cm -1 The characteristic peaks of β-(1,4) glycosidic bond structure, α-(1,4) glycosidic bond structure and D-(1,4) pyranose glucose structure appeared at the β-cyclodextrin grafted chitosan, indicating that β-cyclodextrin and chitosan structures were cross-linked. Figure 2 , Figure 3 and Figure 4 It can be seen that β-cyclodextrin grafted chitosan has a wavelength of 1654 cm -1 The intensity of the C=O absorption peak at 1570 cm -1 There is no -NH2 absorption peak on the left and right, indicating that the -NH2 in chitosan reacts with the C=O of the cross-linking agent glutaraldehyde, further indicating that β-cyclodextrin and chitosan are cross-linked and polymerized.

[0039] The isoniazid electrochemical biosensor prepared in Example 1 was used to screen the experimental conditions: (1) Selection of pulse period The isoniazid electrochemical biosensor prepared in Example 1 was placed in a concentration of 2.0×10 -4 Differential pulse voltammetry was performed in a mol / L isoniazid solution with pulse periods of 0.3s, 0.4s, 0.5s, 0.6s, and 0.7s, respectively. The results are shown in Figure 5 .

[0040] Depend on Figure 5 It can be seen that with the increase of pulse period (0.3s, 0.4s, 0.5s, 0.6s, 0.7s), the current response value of the isoniazid electrochemical biosensor will increase significantly with the increase of pulse period. When the pulse period is 0.6s, the current response value will reach the maximum. When the pulse period continues to increase to 0.7s, the current response value will decrease instead, and the sensitivity will decrease. The optimal pulse period is 0.6s.

[0041] (2) Selection of buffer solution concentration Phosphate buffer solutions with concentrations of 0.05 mol / L, 0.10 mol / L, 0.15 mol / L, 0.20 mol / L, and 0.25 mol / L were selected (the pH of the phosphate buffer solution was adjusted to 4 using a calibrated pH acidity meter). The isoniazid electrochemical biosensor prepared in Example 1 was placed in a solution with a concentration of 2.0×10 -4 mol / L isoniazid solution (dissolved in phosphate buffer solution of different concentrations at pH 4), differential pulse voltammetry scanning was performed within the optimal pulse period. The results are shown in Figure 6 .

[0042] Depend on Figure 6 It can be seen that the oxidation peak current at negative potential undergoes a series of changes in phosphate buffer solutions of different concentrations. The current response change reaches the maximum in 0.10 mol / L phosphate buffer solution, and the electrode sensitivity is the highest, so the optimal phosphate buffer solution concentration is 0.10 mol / L.

[0043] (3) Selection of pH of buffer solution Under the conditions of the optimal pulse period of 0.6s and the phosphate buffer solution concentration of 0.10mol / L, the effect of different pH values ​​(3, 4, 5, 6, 7) of the buffer solution was investigated and characterized by differential pulse voltammetry (DPV). The optimal buffer solution pH was obtained. The results are shown in Figure 7 .

[0044] Depend on Figure 7 It can be seen that starting from pH = 7, as the acidity of the buffer solution increases, the current response value will also increase. When the buffer solution pH = 4, the current response value reaches the maximum and the electrode sensitivity is the highest. When the buffer solution pH = 3, the current response value decreases instead. Therefore, the optimal buffer solution pH is 4.

[0045] Methodology Experiment: (1) Drawing of standard curve Prepare different concentrations (1.0×10 -4 mol / L、2.0×10 -4 mol / L、3.0×10 -4 mol / L、4.0×10 -4 mol / L、5.0×10 -4 mol / L、6.0×10 -4 mol / L) of isoniazid solution, the isoniazid electrochemical biosensor prepared in Example 1 was placed in different concentrations (1.0×10 -4 mol / L、2.0×10 -4 mol / L、3.0×10 -4 mol / L、4.0×10 -4 mol / L、5.0×10-4 mol / L、6.0×10 -4 mol / L) isoniazid solution, and the current was scanned by differential pulse voltammetry, and the current was measured to be 9.52μA, 10.54μA, 11.68μA, 12.52μA, 13.40μA, and 14.80μA, respectively. The standard curve was drawn with the isoniazid solution concentration as the abscissa and the current of the isoniazid electrochemical biosensor as the ordinate, see Figure 8 .from Figure 8 It can be seen that the current of the isoniazid electrochemical biosensor increases with the increase of the concentration of isoniazid solution. The linear equation is: y=1.0234x+8.4947, and the correlation coefficient R 2 is 0.9951, when the concentration of isoniazid solution is 1.0×10 -4 -6.0×10 -4 There is a good linear relationship in the mol / L range.

[0046] (2) Determination of precision The isoniazid electrochemical biosensor prepared in Example 1 detected the isoniazid at a concentration of 1.0×10 - 4 mol / L isoniazid solution was measured continuously for 6 times, and the measured current results were 9.31μA, 9.47μA, 9.46μA, 9.39μA, 9.66μA, and 9.42μA, respectively. The (RSD) value was calculated based on the obtained data, and the calculated result was 1.24%, indicating that the isoniazid electrochemical biosensor has good precision. The precision measurement results are shown in Table 1.

[0047]

[0048] (3) Determination of stability Under the conditions of optimal buffer concentration, pH and optimal pulse period, the isoniazid electrochemical biosensor prepared in Example 1 detected a concentration of 1.0×10 -4 mol / L isoniazid solution, and its current value was measured at different time periods (1h, 4h, 8h, 12h, 24h, and 36h). The measured current values ​​were 10.19μA, 10.01μA, 9.99μA, 9.96μA, 9.53μA, and 9.47μA, respectively. The relative standard deviation (RSD) value of different time periods was calculated based on the results obtained, which was 2.94%, indicating that the isoniazid electrochemical biosensor had good stability within 36h. The stability measurement results are shown in Table 2.

[0049]

[0050] (4) Determination of anti-interference performance The main interfering substance in the electrochemical detection of isoniazid is ascorbic acid (AA), which is an easily oxidized substance coexisting in the sample, so ascorbic acid is selected as the interfering agent. -4 0.0014 g of ascorbic acid was added to a mol / L isoniazid solution to obtain a sample after adding an interfering agent. The isoniazid electrochemical biosensor prepared in Example 1 was used for detection. The current detection result of the sample after adding the interfering agent was 9.519 μA, and the current detection result of the sample without adding the interfering agent was 9.465 μA. It can be seen that the current of the sample after adding the interfering agent is basically unchanged compared with the sample without adding the interfering agent, and the calculated RSD value is 0.40%, which can be judged that the isoniazid electrochemical biosensor has certain anti-interference properties.

[0051] (5) Repeatability determination Prepare 6 portions with a concentration of 1.0×10 -4 mol / L isoniazid solution was detected using the isoniazid electrochemical biosensor prepared in Example 1, and the measured current values ​​were 9.45 μA, 9.52 μA, 9.47 μA, 9.32 μA, 9.46 μA, and 9.42 μA, respectively. The RSD value calculated based on the results was 0.71%, which shows that the isoniazid electrochemical biosensor has good repeatability. The repeatability measurement results are shown in Table 3.

[0052]

[0053] (6) Recovery test Take 10 isoniazid tablets (specification 100 mg / tablet, national medicine standard H50020124, Southwest Pharmaceutical Co., Ltd.), grind into powder, dissolve in a 250 mL volumetric flask with a concentration of 0.10 mol / L and a pH of 4 phosphate buffer solution, filter to remove insoluble matter, discard the initial filtrate, and retain the subsequent filtrate. Measure 2 mL of the isoniazid subsequent filtrate, place it in a 100 mL volumetric flask, and measure it with the isoniazid electrochemical biosensor prepared in Example 1. The current value of the solution is measured to be 13.92 μA. According to the measured current value, the linear equation of the standard curve is y=1.0234x+8.4947, and the corresponding isoniazid concentration is obtained, and the isoniazid mass m1 is calculated to be 0.0036 g. Accurately measure 2mL of the isoniazid filtrate and place it in a 100mL volumetric flask, and make six parallel portions; accurately weigh two portions of isoniazid standard with masses m2 of 0.0029g, 0.0036g, and 0.0043g respectively (equivalent to 80%, 100%, and 120% of m1), add them to the volumetric flask containing 2mL of the isoniazid filtrate, and dilute to a fixed volume in a 100mL volumetric flask with 0.10mol / L phosphate buffer solution (pH=4) as the test sample. The isoniazid electrochemical biosensor prepared in Example 1 was used for determination, and the current values ​​measured were 17.90 μA, 17.76 μA, 18.45 μA, 19.28 μA, 20.46 μA, and 20.82 μA, respectively. The measured current values ​​were substituted into the standard curve linear equation: y=1.0234x+8.4947 to obtain the corresponding INH concentration. The mass m3 of INH in the solution was obtained based on the corresponding INH concentration. The results are shown in Table 4, and the recovery rate formula is as follows: , where P is the sample recovery rate.

[0054]

[0055] (7) Sample analysis Take 2 isoniazid tablets (specification 100 mg / tablet, national medicine standard number H50020124, Southwest Pharmaceutical Co., Ltd.), grind them into powder, dissolve them in 0.10 mol / L, pH=4.00 phosphate buffer solution, transfer them to a 100 mL volumetric flask, dilute to the scale with 0.10 mol / L, pH=4.00 phosphate buffer solution and shake well, filter out insoluble matter, discard the initial filtrate, retain the subsequent filtrate, transfer 4 mL of the subsequent filtrate into a 100 mL volumetric flask, dilute to the scale with 0.10 mol / L, pH=4.00 phosphate buffer solution to make a certain concentration of isoniazid solution as the test solution, take 25 mL of the test solution for testing, and calculate the mass of isoniazid in 25 mL of the test solution according to the specification of isoniazid tablets 100 mg / tablet, mstandard=0.002 g. 25 mL of the solution to be tested was transferred into a small beaker, and the isoniazid electrochemical biosensor prepared in Example 1 was used to scan the solution three times, and the current values ​​were measured to be 14.25 μA, 14.35 μA, and 14.30 μA, respectively. The average value of the three current values ​​measured, 14.30 μA, was substituted into the linear equation y=1.0234x+8.4947, and the concentration of isoniazid in the solution to be tested was calculated to be 5.7×10 -4 mol / L, according to the concentration, the mass of isoniazid in 25mL of the test solution is calculated to be mmeasured = 0.002g, and the labeled amount of isoniazid in isoniazid tablets of this specification is calculated to be 100.0%, which is within the range of the labeled amount of isoniazid in the 2020 edition of the "Chinese Pharmacopoeia" (95.0-105.0%), indicating that the isoniazid electrochemical biosensor has certain application value.

Claims

1. A method for preparing an isoniazid electrochemical biosensor, characterized in that The steps include: (1) After pretreatment, the gold electrode is obtained as a bare gold electrode; (2) Suspending and immersing the bare gold electrode in a 2,3-dimercaptosuccinic acid solution, taking it out, rinsing it, and then drying it to obtain a 2,3-dimercaptosuccinic acid-modified gold electrode; (3) adding β-cyclodextrin and refined chitosan to HCl solution and stirring evenly to obtain a milky white solution; heating the milky white solution until it becomes colorless, adding glutaraldehyde to react, adjusting the pH value, cooling, precipitating, and filtering to obtain β-cyclodextrin grafted chitosan; (4) The gold electrode modified with 2,3-dimercaptosuccinic acid is added to a mixed solution of β-cyclodextrin grafted chitosan and a crosslinking agent, immersed, washed, and dried to obtain an isoniazid electrochemical biosensor.

2. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that The pretreatment in step (1) is performed in sequence: grinding, polishing, first ultrasonic cleaning, drying, second ultrasonic cleaning and rinsing.

3. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that In step (2), the suspension soaking temperature is 3.5-4.5° C., and the suspension soaking time is 22-26 h. The concentration of the 2,3-dimercaptosuccinic acid solution is 0.018-0.022 mol / L.

4. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that In step (3), the ratio of β-cyclodextrin, refined chitosan, HCl solution and glutaraldehyde is 2.9-3.1:0.9-1.1:149-151:3.9-4.1, wherein β-cyclodextrin and refined chitosan are both measured in g, and HCl solution and glutaraldehyde are both measured in mL.

5. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that In step (3), the concentration of the HCl solution is 0.95-1.05 mol / L, and the concentration of glutaraldehyde is 48-52 wt.%.

6. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that In step (3), the heating temperature is 84-86°C, and the heating time is 28-32 min; the reaction temperature is 83-85°C, and the reaction time is 1-1.1 h; and the pH value is adjusted to 7.9-8.

1.

7. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that In step (4), the mixed solution of β-cyclodextrin grafted chitosan and a crosslinking agent is prepared by mixing β-cyclodextrin grafted chitosan and a crosslinking agent, wherein the mass ratio of β-cyclodextrin grafted chitosan to the crosslinking agent is 1:1.1-1.

2.

8. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that In step (4), the cross-linking agent is a mixed solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 0.18-0.22 mol / L, and the concentration of N-hydroxysuccinimide is 0.018-0.022 mol / L.

9. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that The preparation method of the cross-linking agent in step (4) is to dissolve 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a phosphate buffer solution to obtain the cross-linking agent.

10. The method for preparing the isoniazid electrochemical biosensor according to claim 1, characterized in that The soaking time in step (4) is 22-26 hours.

Citation Information

Patent Citations

  • Gold nano-flower modified electrode as well as preparation method and application thereof

    CN107991362A

  • Preparation method and application of EDTA modified magnetic chitosan cyclodextrin adsorbent

    CN111215036A